E-wallet Delivery Technology Architecture Adoption: A Review - Kalaivani Chellappan,; Tharsshinee Elanchselvan,; Asma Abu-Samah, (Penerbit Universiti Kebangsaan Malaysia, 2025)
E-wallet is a fintech digital tool that enables cashless, quick, and easy transactions, and allows users to review and analyze payment histories. However, the expansion of digital wallet usage has contributed to a surge in overspending where users fail to utilize the generated expenditure data to improve personal financial management. The objective of this study is to compare operational features of existing delivery technologies to ensure the best suited delivery technology is adapted into the proposed adaptive money management embedded e-wallet design. A review was conducted to find relevant articles published between 2017 to 2021. The main inclusion criteria were English articles that discuss the applications of NFC, QR code, Digital (online)-only, and/or SMS. The search resulted in 159 articles but only 12 met all the inclusion criteria. The review highlights the advantages and disadvantages of using the three technologies in financial applications. This review suggests that QR payment is most popular, secure, fast, and costeffective compared to NFC and SMS. This makes QR technology the best suited delivery technology for the adaptive management embedded e-wallet that incorporats the four blocks of Fintech technologies namely, blockchain, AI, IoT and RPA.. Overall, a QR code enabled e-wallet can expedite and automate the process of analyzing transactions, thus providing a solution for secure transactions and better money management.